(3OjhGf Ydbegs - (3YdbeI GdaMd , YdbeI Hf YHOg Hf fGTQI Hf bjSs
(3ChdgG (B:s
(3hbGd Ydbeg Hf YHOg jeOM GdMGQK Hf CHj TeQ GdYSGfj, hcGf CSQ CNGg aQMd Edjg WMG Hc bdH aj GdMSGf WQhH HYjO GdTHGH YUQ MGf eTjH s
(3BNQgG (B:s
(3ef bUjOI QGFjI BNQgG(B: (3JQi GdTQ bO Cafi OhGFQ hLgg cVH GdcQi Cafi CfG efg GdMaQ HOJ ShGHb ef ChdGg fYQagG hcHQg aj ShGO Gddjd eSJhQ s
(3GdeDda Jhai YGe (B20 (3bHd GdgLQIs
(3jdjgG bUjOI QGFjg dYHOGdQMef Hf Ydbegs
(3hhQO CjVkG JMJ Qbe (B502(3, (B503(3, (B1303(3, (B1304(3, (B1336(3, (B1866(3, (B1867(3,s
(3GfXQg eY OjhGf GdCYTi s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdCOHs